2019
DOI: 10.1590/1413-81232018243.09462017
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à qualidade de vida de brasileiros e de diabéticos: evidências de um inquérito de base populacional

Abstract: Resumo Buscou-se avaliar as associações entre condições de saúde e características sociodemográficas em relação à qualidade de vida (QV) na população brasileira; bem como estimar os principais fatores associados às chances de uma melhor QV entre diabéticos. Trata-se de um estudo com dados obtidos do inquérito de base populacional realizado no Brasil, em 2008. Foram analisados 12.423 brasileiros, com idade ≥ 20 anos, cujos 935 eram diabéticos. Os desfechos de QV foram mensurados por meio dos componentes sumário… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
4
0
11
Order By: Relevance
“…It is important to note that the presence of chronic diseases can negatively influence the quality of life of older adults, especially in their physical aspects. This fact was observed in patients with DM when compared to the general population (33) .…”
Section: Discussionmentioning
confidence: 64%
“…It is important to note that the presence of chronic diseases can negatively influence the quality of life of older adults, especially in their physical aspects. This fact was observed in patients with DM when compared to the general population (33) .…”
Section: Discussionmentioning
confidence: 64%
“…In the FI group, aspects related to emotional/social support (absence of a partner or spouse) and basic needs for life maintenance and comfort of the living environment (not having daily availability of water and drinking untreated water) were associated with low perceived QoL. Studies indicate that the presence of a partner is associated with better mental health and better perceived QoL, especially in the physical and mental domains, emotional and social support, and can positively assist family socioeconomic status ( 34 , 35 ). A study conducted with 1,492 Dutch people aged 50 years or more observed that Participants who were married or cohabited scored higher in quality-of-life domains, mainly concerned with the psychological and social domains ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nessa perspectiva, o intuito de levantar características de determinada população do ponto de vista socioeconômico se justifica pelo fato de grande parte das morbidades não serem explicadas por fatores isolados e sim por um conjunto de fatores como aspectos relacionados ao modo de viver e a qualidade de vida do indivíduo 11 .…”
Section: Discussionunclassified